Calculations of electron scattering from cadmium - Berrington, M.; Fursa, Dmitry; Bray, Igor; McEachran, R.; Stauffer, A. (2012)
Electron scattering from cadmium atoms has been investigated theoretically using the Convergent Close-Coupling (CCC), Relativistic Optical Potential (ROP) and Relativistic Distorted Wave (RDW) methods. Differential, integrated and ionization cross sections have been calculated between 1 and 500 eV and compared against experimental data. Electron impact coherence parameters have also been calculated and compared against available experiment.